Thirty-Third Annual Meeting American Malacological Union Ottawa, Ontario, Canada July 31- August 4, 1967 (Hello World!, 1967)
It is the custom to publish a full account of the meetings in the AMU Annual Reports and this will be done again this year by the able secretary, Mrs. Margaret C. Teskey. With her permission, the following notes are published here for the convinience of members of the AMU and readers of STERKIANA.